Students’ Motivation in English Learning amid Covid-19 Pandemic: A Systemic Functional Linguistics Perspective - Arsen Nahum Pasaribu (AL-ISHLAH: Jurnal Pendidikan, 2022)
The pandemic of covid-19 has had a negative impact on schooling quality around the world. The lack of student enthusiasm to learn using digital platforms is one issue leading to the low quality of education. Several prior types of research have looked into how students perceive their motivation to learn in the face of pandemic covid-19. However, modal analysis to reveal students' motivation through their written personal views on learning during the epidemic of Covid-19 remains a relatively unexplored area. This research aims to expose the students’ motivation to learn during the outbreak of covid-19 using modality theory. 20 English Department students, Faculty of Language and Arts, University of HKBP Nommensen were involved in this research. The students were assigned to write an essay about their experiences and opinions of learning amid the covid-19 outbreak.   The essay consists of approximately 250 words. The research was conducted in a mixed method. The results showed that the most modality used in the text is probability 39.82%, afterwards frequency 27.60%, obligation 17.19%, and inclination 15.39%, respectively. A medium level or category dominated each type of modality. Regarding polarity, 159 (71.95%) of modal words were in the positive range, and the rest of the modality 62 (28.05%) were located in the negative range. This demonstrates that students' enthusiasm to learn throughout the pandemic was characterized as medium and highly positive. The findings were relatively different from the previous research on the same topic. Most of the research revealed low student motivation amid the covid-19 pandemic. However, this research showed different results that the EFL students were still motivated to study their lessons amid the covid-19 pandemic. The results bring consequences to the future educational research to consider using linguistic perspectives in the research method, especially the application of Systemic Functional Linguistics to reveal the meanings of the students’ perspectives on certain educational issues.